Análise do efeito biológico de nanopartículas de ouro reduzidas com extrato de Punica granatum L. sobre Escherichia coli ATCC 25922 - Cesário, Letícia Miranda (2023)
The rise in antimicrobial resistance has become a critical public health concern, requiring new approaches to face pathogens. Gold nanoparticles (AuNPs) are deemed promising in the fight against pathogenic biofilms due to their unique physicochemical characteristics, which can be tailored for specific purposes. In the present study, we employed the green synthesis of AuNPs, using pomegranate peel extract (Punica granatum L.) as a reducing agent, due to its antioxidant properties and the inherent non-toxicity of the method. For the synthesis of the AuNPs, two techniques were employed: sodium citrate chemical reduction and the green synthesis method using pomegranate extract. The nanoparticles were characterized through spectroscopic and imaging techniques, such as UV-Vis, Raman spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), Inductively Coupled Plasma Mass Spectrometry (ICP-MS), Dynamic Light Scattering (DLS), and Transmission Electron Microscopy (TEM). The phenolic compounds present in the extract and in the AuNPs were identified by HighPerformance Liquid Chromatography coupled to mass spectrometry (HPLC-MS). The success of the AuNP synthesis was initially confirmed by the reddish hue of the resulting colloid and the absorbance pattern in the UV-Vis spectra. Spectroscopic analyses showed the presence of various organic compounds in the pomegranate peel, such as amino acids, phenols, ellagic tannins, and gallic and ellagic acid esters, which participate in the stabilization of the AuNPs. The gold concentration in the nanoparticles was 42.70 μg/mL, while the concentration of pomegranate extract present in the nanoparticles was 380 μg/mL. The AuNPs exhibited a hydrodynamic size in the range of 68.80 nm and a zeta potential of -16.4 mV, indicating stability in aqueous solution. The EC50 value obtained through the DPPH assay proved that the pomegranate extract has high antioxidant activity, greater than that of the Trolox standard. The evaluation of antimicrobial activity was carried out on the Escherichia coli ATCC 25922 strain. The highest concentration of gold nanoparticles with pomegranate extract (170.8 μg/mL) exhibited antimicrobial effect, which, although minimal, caused deformations in the bacterial membrane. In conclusion, the study describes an eco-friendly synthesis of gold nanoparticles using pomegranate extract, which exhibited high antioxidant potential. Although the AuNPs showed limited antimicrobial properties, they emerge as promising candidates for biomedical and nanotechnological applications, requiring additional studies to enhance their potential as antibacterial agents.